1992
DOI: 10.1104/pp.100.2.625
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gibberellin Production in the Fungi Gibberella fujikuroi and Sphaceloma manihoticola by Plant Growth Retardants

Abstract: The effect of different types of plant growth retardants on fungal gibberellin (GA) formation has been studied in cultures of Gibberella fujikuroi and Sphaceloma manihoticola. Quaternary ammonium compounds (chlormequat chloride, mepiquat chloride, Amo-1618), triazoles (uniconazole and several experimental compounds), and the norbornanodiazetine tetcyclacis inhibited GA biosynthesis in both fungal species. Concentrations between 2 x 1iO`and 10-M were required for a 50% inhibition of the production of gibberelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…4 Additionally, the application of chemicals that targeting GA biosynthesis represents a feasible way to control the unwanted longitudinal shoot growth of crops. 5 Paclobutrazol (Pac) 6 and uniconazole (Ucz) 7 are widely used plant growth regulators (their structures are shown in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Additionally, the application of chemicals that targeting GA biosynthesis represents a feasible way to control the unwanted longitudinal shoot growth of crops. 5 Paclobutrazol (Pac) 6 and uniconazole (Ucz) 7 are widely used plant growth regulators (their structures are shown in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Both compounds inhibit GA biosynthesis thereby reducing plant height and inducing the morphological characteristics of GA deficient mutants. [6][7][8] Recent progress on the studies of brassinosteroid (BR) functions has indicated that BRs is a good target for bioengineering of high yield of crops. 9 Analysis the BR-deficient mutants gave evidences that BRs play a key role in promoting plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Th e most used and eff ective type of control, however, is the one that involves the application of chemical growth retardants. Several plant growth regulators labelled for use in fl oriculture, such as the triazoles and pyrimidines, were developed to reduce stem elongation by inhibiting the synthesis of gibberellins (Rademacher 1989(Rademacher , 1992Brown et al 1997). A secondary eff ect linked to the inhibition of gibberellic acid biosynthesis is, for some plant genus including Camellia, an early and enhanced fl owering (Halevy 1983).…”
mentioning
confidence: 99%
“…The number of gibberellin genes available from plants has increased notably in the past few years (reviewed in Avalos eta/., 1997). The enzymes of the gibberellin pathway should be similar in plants and fungi, as suggested by sensitivity to the same inhibitors (Graebe, 1987;Rademacher, 1992). The identification of conserved domains in the kaurene synthase genes of various plants made possible the cloning of their counterpart in the fungus Phaeosphaeria (Kawaide et a/., 1997).…”
Section: Genes and Transcriptionmentioning
confidence: 99%